Increased Frequencies of Myeloid-Derived Suppressor Cells Precede Immunodiscordance in HIV-Infected Subjects - Rosado-Sánchez, Isaac; De Pablo-Bernal, Rebeca; Rull, Anna; Gónzalez, Juan; Moreno, Santiago; Vinuesa, David; Estrada, Vicente; Muñoz-Fernández, María Ángeles; Vidal, Francesc; Leal, Manuel; Pacheco, Yolanda María (Frontiers in Immunology, 2020)
Background: We have previously observed increased levels of inflammatory biomarkers and Th17 as well as Treg cells, but not other T-cell specific alterations, preceding immunodiscordance of successfully-treated HIV-infected subjects. Our hypothesis is that this could be related with potential alterations in Myeloid-Derived Suppressor Cells (MDSCs) and/or monocyte subsets. Methods: We determined the frequencies of MDSCs and monocytes subsets and their expression of several functional markers (CCR2, β7-integrin, IDO, PDL1, CD11b) in HIV-infected subjects before treatment. We additionally analyzed follow-up samples after 24 months of suppressive cART in a subgroup of subjects. Bivariate regressions were performed, and correlations with soluble proinflammatory and bacterial translocation biomarkers, as well as with Th17/Treg ratio and anti-CMV titers were explored. Results: Increased frequencies of MDSCs, but normal distribution of monocyte subsets, preceded immunodiscordance. The expression of several functional markers, such as CCR2, CD16, CD11b and PDL1, on MDSCs and monocyte subsets was altered in this scenario. MDSC and monocyte-related functional markers were associated with soluble biomarkers and T-cells parameters. Several of these cellular alterations were not restored after 24 months of suppressive cART. Conclusion: An early immunosuppressive environment, characterized by the expansion of MDSCs and Tregs, precedes immunodiscordance and is related with a highly inflammatory status.